Canada's Changing Families : Implications for Individuals and Society - Ravanera, Zenaida R.; McQuillan, Kevin (Book collections on Project MUSE., 2006)
"In recent years, two significant trends have had a substantial impact on Canadian families. First, Canadian families have been dramatically altered by high rates of separation and divorce, declining fertility, greater popularity of alternative family arrangements such as cohabitation, and increasing involvement of women in paid labour. Second, changes occurring in the economy and the larger society have brought new pressures to bear on families. In Canada's Changing Families, editors Kevin McQuillan and Zenaida R. Ravenera explore how these developments have altered family life. Using data collected in recent surveys by Statistics Canada, contributors to this volume illustrate how transformed conditions in the labour market have forced families to alter their routines and the division of responsibilities within the household. At the same time, the government, striving to maintain or increase the competitive position of the economy, has moved to control spending, restrain taxes, and reduce deficits. The result has been new demands on the family to provide or supplement services that might otherwise be provided by the state. Canada's Changing Families is an eye-opening study and one of great contemporary relevance."--Pub. desc.